Juridical Review of the Annulment of Arbitral Awards by the District Court: A Case Study of Decision No. 167/Pdt.P/2000/PN.Jkt.Pst - Ervianti, Meliala Nur; Setiadi, Edi; Heniarti, Dini Dewi (Faculty of Law, Universitas Pekalongan, 2025)
one form of alternative dispute resolution that is final and binding. However, in practice, arbitral awards may still be annulled by the district court based on the provisions of Article 70 of Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. This article provides a juridical analysis of the annulment of an arbitral award by the Central Jakarta District Court in case No. 167/Pdt.P/2000/PN.Jkt.Pst. This research employs a normative juridical method with a case study approach. The findings indicate that the annulment by the district court in this case did not fully comply with the annulment provisions stipulated in Article 70, and it potentially undermines the principles of finality and legal certainty in arbitration